Student Ethos in Codes and Everyday Life - Smużewska, Marcelina (INSTED: Interdisciplinary Studies in Education & Society, 2012)
Modern university model faces many problems; it is even said to be undergoing a crisis. The most frequent reasons include commercialization, mass education, bureaucracy, politicization, the development of digital technologies, popularity of postmodernism and critical trends in social sciences. What is sought for are the new, more functional solutions, which would be appropriate for the changing reality. As regards subject dimension a question about the nature of the master-disciple relation is posed. It has a significant impact on the content and coherence of the academic ethos and its student variant. Because of the undertaken studies a student is entitled (and obliged at the same time) to a concrete and sociallyrecognised activity, namely ? the acquisition of knowledge. In this respect, it differs from all formed professional roles, where at best this task is placed at the end of the catalogue of activities ascribed to a given role. However, what is the problem is the fact that often the learner does not know what he/she should be like lacking a personal model. Therefore, there is a risk that without ethical education, i.e. establishing the declarations of proceedings and codes, they will somewhere lose the essence of the role they are fulfilling.